Kimbanguism: An African Understanding of the Bible - Mokoko Gampiot, Aurelien (Signifying (on) Scriptures, 2017)
"A comprehensive study of Kimbanguism, founded by Simon Kimbangu in 1921. Compares it to other African-initiated churches, and examines its role, alongside other global religious movements, in Black liberation"--Provided by publisher.